Seasonal variability of heterogeneous ice formation in stratiform clouds over the Amazon Basin. Issue 13 (4th July 2015) - Seifert, Patric; Kunz, Clara; Baars, Holger; Ansmann, Albert; Bühl, Johannes; Senf, Fabian; Engelmann, Ronny; Althausen, Dietrich; Artaxo, Paulo
Abstract Based on 11 months of polarization lidar observations in the Amazon Basin near Manaus, Brazil (2.3∘S, 60∘W), the relationship between temperature and heterogeneous ice formation efficiency in stratiform clouds was evaluated in the cloud top temperature range between −40 and 0∘C. Between −30 and 0∘C, ice‐containing clouds are a factor of 1.5 to 2 more frequent during the dry season. Free‐tropospheric aerosol backscatter profiles revealed a twofold to tenfold increase in aerosol load during the dry season and a Monitoring Atmospheric Composition and Climate—Interim Implementation reanalysis data set implies that the aerosol composition during the dry season is strongly influenced by biomass burning aerosol, whereas other components such as mineral dust do not vary strongly between the seasons. The injection of smoke accompanied by the likely dispersion of biological material, soil dust, or ash particles was identified as a possible source for the increased ice formation efficiency during the dry season.